Analysis of the Impact of Mining on the Economy and Environmental Degradation in Morowali Regency (A Case Study of PT IMIP) - Anggi Purnomo; Suparman Suparman; Mukhtar Lutfi; Yohan Yohan; Meity Ferdiana Paskual (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2026)
Morowali Regency in Central Sulawesi has emerged as Indonesia’s leading nickel hub through the Indonesia Morowali Industrial Park (PT IMIP), a joint venture with China’s Tsingshan Steel Group. Since 2013, PT IMIP has attracted billions in investment and developed advanced smelters to meet global demand for electric vehicle batteries. While this expansion has boosted economic growth and employment, it has also raised serious environmental concerns. This study analyses the dual impact of nickel mining in Morowali Regency, using 2010–2024 data from the Central Statistics Agency and supporting literature. The objective is to measure the mining sector’s contribution to Gross Regional Domestic Product (GRDP) and evaluate its environmental consequences. A descriptive quantitative approach was applied to examine the relationship between GRDP and the mining sector, while qualitative analysis was used to assess environmental degradation. Results show that GRDP rose sharply from Rp4.10 billion in 2011 to Rp98.79 billion in 2024. Although the mining sector’s share declined from 41.67% to 18.18%, its absolute value increased, driving employment, socio-economic transformation, and business diversification. However, mining activities caused severe environmental damage, including 5,501 hectares of deforestation, marine ecosystem disruption, water and air pollution, and a surge in acute respiratory disease cases to 55,527 in 2024. Waste generation in Bahodopi District reached 40 tonnes per day, with inadequate management infrastructure. The study concludes that sustainable resource management policies are urgently needed to balance economic growth with environmental conservation, recommending stronger regulations, adoption of eco-friendly technologies, and community empowerment.